Neuroprotective effects of electroacupuncture on hypoxic-ischemic encephalopathy in newborn rats association with increased expression of mTOR - Xu, Tao; Zhao, Na; Liu, Jing-Dong; Xiao-Mei, Mo; Zhang, Hui; Qin, Peng-Fei; Feng, Xiang-Chun; Sun, Qing (Bangladesh Journal of Pharmacology, 2016)
In this study, we observed the therapeutic effects of acupuncture and investigated the underlying molecular mechanisms by constructed a hypoxic-ischemic encephalopathy (HIE) animal model. In the electroacupuncture group, mTOR expression increased since 1d, and continued to rise till the 21st day. All of the differences were significantly (p<0.05 vs the model group). Meanwhile, mTOR expression was analyzed by Western blotting. There was statistical significance between the model group and the electroacupuncture group in the four time periods (p<0.05). The results provide evidence that electroacupuncture treatment protected cortical neurons against HIE-induced neuronal damage and degenerative changes in rats, which is in association with activation of mTOR both at the mRNA level and protein level. Therefore, electroacupuncture may become a potential therapeutic strategy for HIE of newborn.